Preparation of future educators to form logical and mathematical concepts of children of the advanced preschool age (Pedagogy of Higher and Secondary Education, 2013)
Ischenko L. V. Preparation of future educators to form logical and mathematical concepts of children of the advanced preschool age.Article is devoted to acquaintance of future tutors with effective forms and methods of formation of logical-mathematical concepts of children of the advanced preschool age. Efficiency of use in practical work of tutors of kindergartens of nonconventional methods of training (problem situations of a task, a task with elements of search, a task joke, a task with a fantastic plot) is proved.
Keywords: logik-mathematical development; boolean operations of concept «readiness to school»